Ultra-light calcium silicate insulation board and preparation method thereof

Through pressurized foaming-pressure relief foaming process and physical-chemical collaborative foaming technology, combined with ultra-refined raw materials and nanomaterials, the problems of high density, low strength and high thermal conductivity of inorganic insulation materials were solved, and ultralight calcium silicate insulation board with excellent performance was prepared.

CN119841609APending Publication Date: 2025-04-18WUHAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510012204.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Existing inorganic insulation materials have problems such as high density, low strength and high thermal conductivity, making it difficult to achieve ultra-lightweight and ultra-low thermal conductivity design.

Method used

The pressurized foaming-pressure relief foaming process is adopted, combined with physical-chemical collaborative foaming technology, ultra-refined calcium and siliceous raw materials are used, and nanoquartz sand and nano calcium carbonate are introduced as pore wall reinforcement components. Through the high-temperature calcium-silicon autoclaved maintenance system, the mechanical properties and thermal conductivity of the material are improved.

Benefits of technology

Ultralight calcium silicate insulation board with a bulk weight of ≤150kg/m3, a compressive strength of ≥300kPa, and a thermal conductivity of ≤0.045W/(m·K) was prepared. Its performance was better than that of commonly used inorganic insulation materials and had Class A non-combustible fire resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention discloses an ultra-light calcium silicate insulation board and a preparation method thereof. The ultra-light calcium silicate insulation board is mainly prepared from the following components in parts by weight through a pressurization foaming-pressure relief foaming process: 21 to 25 parts of an ultra-fine calcium raw material, 26 to 34 parts of an ultra-fine siliceous raw material, 0.5 to 0.8 part of a dispersing agent, 0.2 to 0.4 part of a surfactant, 0.1 to 0.3 part of an emulsion stabilizer, 2.5 to 3.1 parts of a hole wall reinforcing component, 4.2 to 5.6 parts of a foaming agent and 36 to 42 parts of water. On the basis of a physical-chemical coordinated regulation and control method for an internal pore structure of a material and through an inert nano material modified foam technology, the ultra-light design of the calcium silicate insulation board is achieved, meanwhile, the mechanical property of the calcium silicate insulation board is greatly improved, the volume weight of the obtained ultra-light calcium silicate insulation board is smaller than or equal to 150 kg / m < 3 >, the compressive strength is larger than or equal to 300 kPa, and the ultra-light calcium silicate insulation board is A-grade non-combustible and has the good application prospect. The heat conductivity coefficient is less than or equal to 0.045 W / (m.K), and the performance is superior to that of the current common inorganic thermal insulation material
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to an ultra-light calcium silicate insulation board and a preparation method thereof. Background Art

[0002] In 2020, the national building operation phase carbon emissions were 2.16 billion tons, accounting for 21.7% of the country's total carbon emissions. Therefore, it is an important measure to promote ultra-low / near-zero energy consumption buildings, improve my country's building energy conservation level, and reduce building operation energy consumption and carbon emissions.

[0003] Insulation materials are an important material basis for achieving ultra-low / near-zero energy consumption buildings and building energy conservation. Although new high-efficiency insulation materials such as aerogels and vacuum insulation panels have extremely low thermal conductivity, they have key problems such as high cost, complex construction, and easy performance attenuation. Organic materials such as expanded polystyrene have good thermal insulation effects, low prices, convenient construction, and are widely used, but they are flammable and difficult to meet Class A non-combustible standards, posing a fire hazard. Cement-based insulation materials have the advantages of low cost and non-combustibility. Their thermal conductivity is 0.08-0.22W / m·K, which is significantly higher than organic insulation materials (0.025-0.042W / m·K). On the other hand, with the promotion of ultra-low / near-zero energy consumption buildings and the further improvement of building energy conservation and fire safety levels, the demand for new inorganic insulation materials with ultra-low thermal conductivity and non-combustibility has increased year by year, especially for energy-saving renovation of old cities, and the market demand is huge. Therefore, it is of great significance to break through the current dilemma that organic insulation materials have low thermal conductivity but are not fireproof, and inorganic insulation materials are fireproof but have high thermal conductivity, and provide a new preparation method for insulation boards. Summary of the invention

[0004] In view of this, the present invention aims to provide an ultra-light calcium silicate insulation board to solve the industry problems of existing inorganic insulation materials such as high density, low strength and high thermal conductivity.

[0005] To achieve the above object, the technical solution of the present invention is achieved as follows:

[0006] An ultra-light calcium silicate insulation board is mainly prepared from the following components by weight through a pressure foaming-pressure release foaming process: 21-25 parts of ultra-fine calcium raw materials, 26-34 parts of ultra-fine silicon raw materials, 0.5-0.8 parts of dispersant, 0.2-0.4 parts of surfactant, 0.1-0.3 parts of emulsifier stabilizer, 2.5-3.1 parts of pore wall reinforcement component, 4.2-5.6 parts of gas generating agent and 36-42 parts of water.

[0007] Optionally, the ultrafine calcium raw material is one or more of quicklime, carbide slag and silicate cement, which has a CaO content of ≥65% and a median particle size of ≤5 μm; the ultrafine silicon raw material is one or more of slag, silica fume and quartz sand, which has a SiO content of ≥65% and a median particle size of ≤5 μm. 2 Content ≥90%, median particle size ≤3μm.

[0008] The present invention adopts an ultra-fine treatment process to reduce the particle size of calcium raw materials and silicon raw materials with low reaction activity, thereby greatly enhancing their reaction activity, which is conducive to rapid reaction during the pressurization-decompression preparation process, and then forms a gelling substance on the foam surface, achieving the purpose of stabilizing the foam and accelerating hardening. It effectively solves the problem that calcium / silicon raw materials from conventional sources have low reaction activity and cannot form a solid sealing layer on their surface before the foam becomes unstable, and under the pressurization-decompression process, the foam becomes more thermodynamically unstable and more likely to burst after a small expansion.

[0009] Optionally, the surfactant is prepared by mixing animal protein and sodium dodecyl sulfate in a mass ratio of 1:1.

[0010] Optionally, the emulsion stabilizer is prepared by mixing polyoxyethylene ether and guar gum in a mass ratio of 2:1.

[0011] Optionally, the pore wall reinforcement component is formed by mixing nano-quartz sand and nano-calcium carbonate in a mass ratio of 3:1; the median particle size of the nano-quartz sand is 60-90 nm, and the median particle size of the nano-calcium carbonate is 40-80 nm.

[0012] The present invention introduces nanomaterials to strengthen the pore walls. Unlike conventional technical means, this nanomaterial is a high-silicon inert raw material with a wide source and low cost. During the material preparation process, this nanomaterial adheres to the foam and plays a role in stabilizing the foam. After entering the maintenance stage, this nanomaterial can undergo a chemical reaction between the foam pore walls to generate hydration products, which further improves the pore wall strength. This effectively solves the problem of low strength of thermal insulation materials after ultra-light design.

[0013] Optionally, the gas generating agent is a hydrogen peroxide solution having a solid content of 30%.

[0014] The present invention adopts a pressurization-pressure relief process, combined with physical-chemical synergistic foaming. Under pressurized conditions, the prefabricated foam produced by the surfactant expands slightly to produce foam with a relatively large pore size. Hydrogen peroxide undergoes a chemical reaction during the exothermic reaction to produce tiny bubbles. After pressure regulation, the tiny bubbles also expand, complementing the above-mentioned foam with large pore sizes and optimizing the distribution of the foam pore size structure. Through the synergy of these two means, ultra-light and ultra-low thermal conductivity is achieved, which effectively solves the problem that conventional calcium / silicon raw materials cannot achieve ultra-light and ultra-low thermal conductivity design due to their natural properties, such as density, thermal conductivity, etc.

[0015] The second object of the present invention is to provide a method for preparing the above-mentioned ultra-light calcium silicate insulation board, the preparation method comprising the following steps:

[0016] 1) pre-dissolving the surfactant, the emulsion stabilizer and the pore wall strengthening component in part of the water, and then placing them in a pressure barrel A with a pressure of 0.12-0.16 MPa and rapidly stirring them to obtain a uniform and fine prefabricated foam;

[0017] 2) The calcareous raw material and the siliceous raw material are respectively subjected to ultrafine treatment by wet grinding process to obtain the ultrafine calcareous raw material and the ultrafine siliceous raw material; the ultrafine calcareous raw material and the ultrafine siliceous raw material are uniformly mixed to obtain ultrafine powder;

[0018] 3) placing the ultrafine powder, the dispersant, the gas generating agent and the remaining water in a pressure barrel B having a pressure equal to that of the pressure barrel A, and stirring and mixing them uniformly to obtain a slurry;

[0019] 4) opening the connecting valve between the pressure barrel A and the pressure barrel B, so that the slurry and the prefabricated foam are evenly mixed in the pressure barrel A to obtain a foaming slurry;

[0020] 5) Open the pressure relief valve of the pressure barrel A to allow the foamed slurry to expand under normal pressure, and then cast it into shape. After the formed foamed slurry hardens, it is pressure-steamed and cured, and then cut into a desired shape to obtain an ultra-light calcium silicate insulation board.

[0021] Optionally, the stirring rate of the rapid stirring in step 1) is 600-800 r / min, and the stirring time is 90-120 s; the stirring rate of the stirring in step 3) is 200-300 r / min, and the stirring time is 60-120 s.

[0022] Optionally, the grinding medium used in the wet grinding process in step 2) is zirconia grinding balls, the grinding speed is 300-500r / min, and the grinding time is 20-30min; the mass of the zirconia grinding balls is 3 times the total weight of the calcium raw material and the silicon raw material; the grading of the zirconia grinding balls is 2.4mm:1.4mm:0.8mm=1:1:2.

[0023] Optionally, the curing temperature of the pressure steam curing in step 5) is 180° C., the humidity is 100%, the pressure is 1.2 MPa, and the curing time is 8-12 h.

[0024] The bulk density of the ultra-light calcium silicate insulation board obtained by the method of the present invention is ≤150kg / m 3 , compressive strength ≥300kPa, combustion grade is Class A non-flammable, thermal conductivity ≤0.045W / (m·K).

[0025] Preparation mechanism of the present invention:

[0026] The present invention is based on the pressure foaming-pressure relief foaming technology. The prefabricated foam modified by inert nanoparticles is placed in a pressure barrel, so that it undergoes an external environment change from high pressure to low pressure. When the pressurized foam is exposed to a conventional environment, it undergoes uniform expansion, and its foam density is greatly reduced. In addition, a spontaneous gas component is introduced into the pressurized slurry. During the gasification process, the bubbles inside the slurry undergo a pressurization-pressure relief process to achieve micro-expansion. Based on the above-mentioned physical-chemical synergistic pressure-controlled internal pores of the material, an ultra-lightweight design of the material matrix is ​​achieved. Then, a high-temperature calcium-silicon autoclave curing system is adopted to induce the directional generation of products inside the material. In this process, the inert nanoparticles used to modify the foam undergo a chemical reaction under high temperature and high pressure conditions to form a dense structure between the pore walls, greatly improving the mechanical properties of the calcium silicate board.

[0027] Compared with the prior art, the ultra-light calcium silicate insulation board of the present invention has the following advantages:

[0028] 1. The present invention is based on a method of physical-chemical coordinated regulation of the internal pore structure of the material. A pressure field is introduced into the process, and the influence of atmospheric pressure changes on bubbles is utilized to control the internal pores of the material in the air pressure dimension, ultimately achieving an ultra-lightweight design of the material matrix. In addition, the present invention enhances the stability of the prefabricated foam through the use of inert nanomaterial modified foam technology. In the high-temperature and high-pressure calcium-silicon reaction stage, the inert nanomaterial undergoes a chemical reaction to form a dense structure on the pore wall, thereby achieving improved mechanical properties. The combined effect of the above mentioned materials successfully produced a bulk density of ≤150kg / m 3 The ultra-light calcium silicate insulation board has a compressive strength of ≥300kPa, is Class A non-flammable, and has a thermal conductivity of ≤0.045W / (m·K). Its performance is better than the currently commonly used inorganic insulation materials.

[0029] 2. The present invention uses calcium and silicon raw materials as basic materials and introduces a large amount of solid waste, which increases the low-carbon properties of the product obtained by the present invention and greatly reduces its preparation cost, which is conducive to its popularization and application. DETAILED DESCRIPTION

[0030] In order to enable those skilled in the art to better understand the technical solutions and technical effects of the present invention, several embodiments are provided below. Obviously, what is described below is only an embodiment and does not limit the protection scope of the present invention.

[0031] Table 1 shows the raw material ratios of the ultra-light calcium silicate insulation board of Examples 1 to 6 of the present invention and the applied pressures of the pressure barrel A and the pressure barrel B. In each example, the surfactant is formed by mixing animal protein and sodium dodecyl sulfate in a mass ratio of 1:1; the emulsifier stabilizer is formed by mixing polyoxyethylene ether and guar gum in a mass ratio of 2:1; the pore wall reinforcement component is formed by mixing nano-quartz sand and nano-calcium carbonate in a mass ratio of 3:1, and the median particle size of the nano-quartz sand is 60nm, and the median particle size of the nano-calcium carbonate is 40nm; the gas generating agent is a hydrogen peroxide solution, and its solid content is 30%.

[0032] Table 1

[0033]

[0034] Table 2 shows the technical indicators and wet grinding process parameters of the calcium raw materials and silicon raw materials used in the ultra-light calcium silicate insulation boards of Examples 1 to 6 of the present invention.

[0035] Table 2

[0036]

[0037] The ultra-light calcium silicate insulation board of Examples 1 to 6 of the present invention is specifically prepared by the following method:

[0038] 1) According to the raw material ratio in Table 1, the surfactant, emulsion stabilizer and pore wall reinforcement component were pre-dissolved in 15 parts of water, and then placed in a pressure barrel A and rapidly stirred at a stirring speed of 800 r / min for 90 seconds, wherein the pressure in the pressure barrel A is as shown in Table 1, and a uniform and fine prefabricated foam was obtained;

[0039] 2) The calcium raw material and the silicon raw material are respectively subjected to ultrafine treatment by wet grinding process to obtain ultrafine calcium raw material and ultrafine silicon raw material, wherein the mass of the zirconium oxide grinding ball used in the wet grinding process is 3 times the total weight of the calcium raw material and the silicon raw material, and the gradation is 2.4mm:1.4mm:0.8mm=1:1:2 (by mass), and the wet grinding machine speed and wet grinding time are shown in Table 2; the obtained ultrafine calcium raw material and ultrafine silicon raw material are uniformly mixed according to the raw material ratio in Table 1 to obtain ultrafine powder;

[0040] 3) According to the raw material ratio in Table 1, the ultrafine powder, dispersant, gas generating agent and remaining water are placed in a pressure barrel B with a pressure equal to that of the pressure barrel A and stirred at a stirring rate of 300 r / min for 120 s to mix them evenly to obtain a slurry;

[0041] 4) Open the connecting valve between pressure barrel A and pressure barrel B. At this time, the slurry in pressure barrel B flows into pressure barrel A. After the slurry completely flows into pressure barrel A, continue stirring for 120 seconds to mix the slurry and prefabricated foam in pressure barrel A evenly to obtain a foaming slurry;

[0042] 5) Open the pressure relief valve of pressure barrel A to allow the foamed slurry to expand under normal pressure, and then cast it into shape. After the formed foamed slurry hardens, it is autoclaved and cured at 180°C, 100% humidity, and 1.2MPa pressure for 12 hours, and then cut into the required shape to obtain an ultra-light calcium silicate insulation board.

[0043] Samples were prepared according to the above ratio, and then the dry density, compressive strength and thermal conductivity of the samples of Examples 1-6 and Comparative Example 1 were tested with reference to the standard "Test method for properties of autoclaved aerated concrete" (GB / T11969-2020) and the standard "Determination of steady-state thermal resistance and related properties of insulating materials - Protected hot plate method" (GB / T10294-2008). The results are shown in Table 3.

[0044] Table 3

[0045] Example <![CDATA[Dry density (kg / m 3 )]]> Compressive strength(kPa) Thermal conductivity (W / (m·K)) Example 1 148 342 0.042 Example 2 131 326 0.039 Example 3 136 332 0.041 Example 4 128 312 0.039 Example 5 142 318 0.042 Example 6 122 305 0.037 Comparative Example 1 228 405 0.065 Comparative Example 2 185 272 0.053 Comparative Example 3 265 362 0.078

[0046] As can be seen from Table 3, the ultra-light calcium silicate insulation board prepared by the present invention has a bulk density of ≤150kg / m3, a compressive strength of ≥300kPa, and is Class A non-flammable, with a thermal conductivity of ≤0.045W / (m·K). Compared with the comparative example, the pressure change introduced in the present invention effectively reduces the bulk density of the calcium silicate insulation board, optimizes the pore structure, and contributes to its low thermal conductivity design. The present invention provides a new idea for breaking through the current dilemma of high bulk density and thermal conductivity of conventional inorganic insulation materials.

[0047] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. An ultra-light calcium silicate insulation board, characterized in that: The invention is mainly prepared from the following components by weight through a pressure foaming-pressure releasing foaming process: 21-25 parts of ultrafine calcium raw material, 26-34 parts of ultrafine silicon raw material, 0.5-0.8 parts of dispersant, 0.2-0.4 parts of surfactant, 0.1-0.3 parts of emulsifier stabilizer, 2.5-3.1 parts of pore wall reinforcing component, 4.2-5.6 parts of gas generating agent and 36-42 parts of water.

2. The ultra-light calcium silicate insulation board according to claim 1, characterized in that: The ultrafine calcium raw material is one or more of quicklime, carbide slag and silicate cement obtained by ultrafine treatment, and its CaO content is ≥65% and the median particle size is ≤5μm; the ultrafine silicon raw material is one or more of slag, silica fume and quartz sand obtained by ultrafine treatment, and its SiO2 content is ≥90% and the median particle size is ≤3μm.

3. The ultra-light calcium silicate insulation board according to claim 1, characterized in that: The surfactant is prepared by mixing animal protein and sodium dodecyl sulfate in a mass ratio of 1:

1.

4. The ultra-light calcium silicate insulation board according to claim 1, characterized in that: The emulsion stabilizer is prepared by mixing polyoxyethylene ether and guar gum in a mass ratio of 2:

1.

5. The ultra-light calcium silicate insulation board according to claim 1, characterized in that: The pore wall reinforcement component is formed by mixing nano-quartz sand and nano-calcium carbonate in a mass ratio of 3:1; the median particle size of the nano-quartz sand is 60-90nm, and the median particle size of the nano-calcium carbonate is 40-80nm.

6. The ultra-light calcium silicate insulation board according to claim 1, characterized in that: The gas generating agent is a hydrogen peroxide solution with a solid content of 30%.

7. A method for preparing the ultra-light calcium silicate insulation board according to any one of claims 1 to 6, characterized in that: The following steps are involved: 1) pre-dissolving the surfactant, the emulsion stabilizer and the pore wall strengthening component in part of the water, and then placing them in a pressure barrel A with a pressure of 0.12-0.16 MPa and rapidly stirring them to obtain a uniform and fine prefabricated foam; 2) The calcareous raw material and the siliceous raw material are respectively subjected to ultrafine treatment by wet grinding process to obtain the ultrafine calcareous raw material and the ultrafine siliceous raw material; the ultrafine calcareous raw material and the ultrafine siliceous raw material are uniformly mixed to obtain ultrafine powder; 3) placing the ultrafine powder, the dispersant, the gas generating agent and the remaining water in a pressure barrel B having a pressure equal to that of the pressure barrel A, and stirring and mixing them uniformly to obtain a slurry; 4) opening the connecting valve between pressure barrel A and pressure barrel B, so that the slurry and the prefabricated foam are evenly mixed in the pressure barrel A to obtain a foaming slurry; 5) Open the pressure relief valve of pressure barrel A to expand the foamed slurry under normal pressure, and then cast it into shape. After the formed foamed slurry hardens, it is pressure-steamed and cured, and then cut into a desired shape to obtain an ultra-light calcium silicate insulation board.

8. The method for preparing the ultra-light calcium silicate insulation board according to claim 7, characterized in that: The stirring rate of the rapid stirring in step 1) is 600-800 r / min, and the stirring time is 90-120 s; the stirring rate of the stirring in step 3) is 200-300 r / min, and the stirring time is 60-120 s.

9. The method for preparing the ultra-light calcium silicate insulation board according to claim 7, characterized in that: The grinding medium used in the wet grinding process in step 2) is zirconia grinding balls, the grinding speed is 300-500r / min, and the grinding time is 20-30min; the mass of the zirconia grinding balls is 3 times the total weight of the calcium raw material and the silicon raw material; the grading of the zirconia grinding balls is 2.4mm:1.4mm:0.8mm=1:1:

2.

10. The method for preparing the ultra-light calcium silicate insulation board according to claim 7, characterized in that: The curing temperature of the autoclave curing in step 5) is 180° C., the humidity is 100%, the pressure is 1.2 MPa, and the curing time is 8-12 h.